Synthesis, spectral characterization, molecular structure, HOMO-LUMO, MEP and NLO analysis of some (E)-N-(4-Fluoro-3-Phenoxybenzylidene)- substituted benzenamines - Raj, G. Jesu Retna; Jayanthi, P.; Sekar, M. (International Journal of Advanced Chemistry, 2016)
In this work, (E)-N-(4-Fluoro-3-Phenoxybenzylidene)-substituted benzenamines (1-6) have been synthesized and characterized by IR, 1H and 13C NMR spectral studies. Density functional theory (DFT) has been used to optimize geometrical parameters, atomic charges, vibrational wavenumbers and intensity of vibrational bands. The molecular properties HOMO-LUMO, MEP and atomic charges of carbon, nitrogen and oxygen were calculated using B3LYP/6-311G (d, p) basis set. The polarizability and first order hyperpolarizability of the title Compounds were calculated and interpreted.